2022
DOI: 10.1111/tan.14733
|View full text |Cite
|
Sign up to set email alerts
|

Higher risk for chronic graft‐versus‐host disease (GvHD) in HLA‐G mismatched transplants following allogeneic hematopoietic stem cell transplantation: A retrospective study

Abstract: Introduction Graft‐versus‐host disease (GvHD) is a major complication after allogeneic hematopoietic stem cell transplantation (allo‐HSCT) and is highly influenced by the degree of HLA matching between recipient and donor. The HLA‐class Ib molecule HLA‐G has been shown to promote tolerogenicity through its interaction with inhibitory receptors found on several immunocompetent cells. We hypothesized that in an allo‐HSCT setting, HLA‐G mismatches may negatively impact the HLA‐G‐mediated tolerogenicity either due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The so-called “non-classical” HLA loci (i.e., HLA-G and -E) might also have a clinical impact [ 21 , 22 ], although this is beyond the scope of the present article.…”
Section: Definitions Of Hla Mismatch In Allo-hsctmentioning
confidence: 99%
“…The so-called “non-classical” HLA loci (i.e., HLA-G and -E) might also have a clinical impact [ 21 , 22 ], although this is beyond the scope of the present article.…”
Section: Definitions Of Hla Mismatch In Allo-hsctmentioning
confidence: 99%
“…Expression levels and polymorphisms in MICA, MICB, HLA-E and HLA-G have been associated with autoimmune diseases (314), infections (1523) and susceptibility to cancer (2433). There is also growing evidence that MICA, MICB and HLA-G function as transplantation antigens and that their polymorphism and matching may be associated with outcomes of transplantation (3437). Moreover, genetic association studies focusing on single nucleotide polymorphisms (SNPs) in the MHC region have identified polymorphisms in the class I region outside of the classical HLA genes that are associated for example with hematopoietic stem cell transplantation (HSCT) outcomes and risk for graft-versus-host disease (GVHD) (3840), as well as autoimmune diseases (4143).…”
Section: Introductionmentioning
confidence: 99%
“…There is also growing evidence that MICA, MICB and HLA-G function as transplantation antigens and that their polymorphism and matching may be associated with outcomes of transplantation (34)(35)(36)(37).…”
Section: Introductionmentioning
confidence: 99%